77 Evaluating virtual family-centered rounds effectiveness, efficiency and usability during the COVID-19 pandemic. (21st October 2022) - Buba, Melanie; Dulude, Catherine; Sutherland, Stephanie; Newhook, Dennis; Attef, Maryam
Abstract: Background: Virtual care has seen exponential growth since the onset of the COVID-19 pandemic, however, the evaluation of virtual care tools and services is lacking, particularly in the inpatient setting. In April 2020, we virtualized our in-person family-centered rounds (FCR) process and demonstrated the ability to perform virtual family-centered rounds (vFCR). In this study, we evaluate vFCR against the accepted standard of in-person FCR to ensure high quality care is maintained and encourage adoption by health care providers, administrators, patients and caregivers. Objectives: The objective of this study is to compare vFCR to established core components and timing for in-person FCR. Perceptions of overall satisfaction, safety and technology usability were also explored. Design/Methods: This is a mixed methods process evaluation of vFCR. Data collection was through virtual and in-person observation and post-vFCR survey of participants. Virtual observations focused on timing and adherence to core components of FCR, while in-person naturalistic observations focused on technology interaction and usability. Observation data underwent quantitative and content analysis. Data from post-vFCR questionnaires were subject to descriptive statistical analysis and content analysis of free-text responses. Results: Sixty-two vFCR were observed virtually and 35 vFCR were observed in-person. Adherence to the core components of FCR during vFCR was variable (Table 1). Mean duration of a single patient round was 8.44 ± 4.93 minutes, with a mean transition time between patients of 3.96 ± 2.96 minutes. One hundred and four surveys were completed (76% response rate), 42 by patients and caregivers and 62 by members of the interdisciplinary medical team. The majority (93%) of respondents surveyed were satisfied or very satisfied with vFCR, and 67% felt it was important or very important to do FCR virtually during the pandemic to keep people safer. Importantly, vFCR was perceived by 96% of medical team members as supporting shared decision making with patients and caregivers, and 78% of patients/caregivers felt like a valued partner in their (child's) care. Virtual family-centered rounds technology was perceived as easy or very easy to use by 95% of respondents. Additional positive and negative comments were submitted by 38% of respondents about their experience with vFCR (Figure 1). Conclusion: Virtual family-centered rounds afford adherence to the core components of family-centered rounds. Satisfaction with vFCR and perceived usability of vFCR technology were both highly rated. Respondents also felt vFCR were important for safety during the pandemic. Rounds duration and transition times between patients were seen as opportunities for improvement. Observation and questionnaire data suggest the efficiency and quality of vFCR may be optimized through routine training on the rounding process and technology, as well as recognition of family-centered rounds as a component of inpatient pediatric care that should be prioritized.